Pelatihan Kreativitas Pendidik dalam Mendesain Media Pembelajaran Modern pada Guru - Saragih, Nurul Azmi; Dewi, Ika Sandra; Handayani, Aminda Tri (TAAWUN, 2024)
This service aims to practice the creativity of educators in designing modern learning media for elementary school teachers. There are five stages of the service method used: the preliminary stage, the socialization and audience stage, the preparation and implementation stage of counseling, the activity stage, the results presentation stage, and the final evaluation. The activity was carried out by presenting material on educators’ creativity in designing modern learning media. The results of the service can be seen from the calculation of the pre-test and post-test questionnaires, both before and after being given the material, showing a significant difference in the numbers from the pre-test which did not fully understand the usefulness of one’s creativity in designing learning media into maximum numbers after being given the understanding to utilize creativity. themselves in designing modern learning media using sophisticated technology according to current developments.